OsRAD51C is essential for double-strand break repair in rice meiosis - Tang, Ding; Miao, Chunbo; Li, Yafei; Wang, Hongjun; Liu, Xiaofei; Yu, Hengxiu; Cheng, Zhukuan (Frontiers in Plant Science, 2014)
RAD51C is one of the RAD51 paralogs that plays an important role in DNA double-strand break repair by homologous recombination. Here, we identified and characterized OsRAD51C, the rice homolog of human RAD51C. The Osrad51c mutant plant is normal in vegetative growth but exhibits complete male and female sterility. Cytological investigation revealed that homologous pairing and synapsis were severely disrupted. Massive chromosome fragmentation occurred during metaphase I in Osrad51c meiocytes, and was fully suppressed by the CRC1 mutation. Immunofluorescence analysis showed that OsRAD51C localized onto the chromosomes from leptotene to early pachytene during prophase I, and that normal loading of OsRAD51C was dependent on OsREC8, PAIR2, and PAIR3. Additionally, ZEP1 did not localize properly in Osrad51c, indicating that OsRAD51C is required for synaptonemal complex assembly. Our study also provided evidence in support of a functional divergence in RAD51C among organisms.